Understanding the aids pandemia in the last 25 years - Pinto, Agnes Caroline S; Pinheiro, Patrícia NC; Pinheiro, Patrícia NC; Vieira, Neiva FC; Alves, Maria Dalva S (Brazilian Journal of Sexually Transmitted Diseases, 2007)
Introduction: along the years the acquired immunodeficiency syndrome (aids) has been changing its profile, and gaining knowledge of the path ofthe aids pandemic is something that called a lot of attention to us. Objective: understand the aids pandemic in Brazil over the twenty-five years of itsexistence. Methods: it is a descriptive research, with documental approach, which used virtual libraries and books’s articles as sources, with a total of34 references in the months of November to December of 2006. The study of the epidemic considered the aspects involved form when it first appea-red in Brazil, in the decade of 1980, together with the public politics involved in this pandemic, as well as the appearance of HIV, the introduction ofthe anti-retrovirus and the new tendencies: interiorização, feminização, heterosexual, pauperização and, more recently juvenização. Results: theywere divided in four topics: the origin of HIV, the new tendencies: what changed?, the anti-retrovirus medicines and the public politics. Based on thedata, it was found that the official responses to aids, since its breakthrough in Brazil, are found at different stages and, with a lot of difficult, it wasestablished politics whose main characteristic is the participation of the population. Conclusion: from this study it is considered that the politicalcommitment and to the local communities’real mobilization will only be successful and make great difference if there is an understanding on thebehalf of the population.